Public Sector Pensions - Rhodes, Gerald (Book collections on Project MUSE., 1965)
This is the first book to offer a fundamental analysis of public sector schemes. It takes a new look at a whole trange of problems affecting the retirement benefits of most of the population and ends with some very challenging, positive proposals.